Insights Into the Evolution of Picocyanobacteria and Phycoerythrin Genes (mpeBA and cpeBA) - Sánchez-Baracaldo, Patricia; Bianchini, Giorgio; Di Cesare, Andrea; Callieri, Cristiana; Chrismas, Nathan A. M. (Frontiers in Microbiology, 2019)
Marine picocyanobacteria, Prochlorococcus and Synechococcus, substantially contribute to marine primary production and have been the subject of extensive ecological and genomic studies. Little is known about their close relatives from freshwater and non-marine environments. Phylogenomic analyses (using 136 proteins) provide strong support for the monophyly of a clade of non-marine picocyanobacteria consisting of Cyanobium, Synechococcus and marine Sub-cluster 5.2; this clade itself is sister to marine Synechococcus and Prochlorococcus. The most basal lineage within the SynPro clade, Sub-Cluster 5.3, includes marine and freshwater strains. Relaxed molecular clock (SSU, LSU) analyses show that while ancestors of the SynPro clade date as far back at the end of Pre-Cambrian, modern crown groups evolved during Carboniferous and Triassic. Comparative genomic analyses reveal novel gene cluster arrangements involved in phycobilisome (PBS) metabolism in freshwater strains. Whilst PBS genes in marine Synechococcus are mostly found in one type of phycoerythrin (PE) rich gene cluster (Type III), strains from non-marine habitats, so far, appeared to be more diverse both in terms of pigment content and gene arrangement, likely reflecting a wider range of habitats. Our phylogenetic analyses show that the PE genes (mpeBA) evolved via a duplication of the cpeBA genes in an ancestor of the picocyanobacteria and of the symbiotic strains Synechococcus spongiarum. A ‘primitive’ Type III-like ancestor containing (cpeBA and mpeBA) had thus evolved prior to the divergence of the SynPro clade and S. spongiarum. During the diversification of Synechococcus lineages, losses of mpeBA genes may explain the emergence of pigment cluster Types II, IIB and III in both marine and non-marine habitats, with few Lateral Gene Transfer events in specific taxa.